Soluble ST2 as a Marker of Subclinical Right Ventricular Dysfunction in Pulmonary Hypertension Associated With Congenital Heart Disease - Fadhil Alfino Azmi; Mefri Yanni; Kino Kino; Hirowati Ali (Jurnal Kardiologi Indonesia, 2026)
Background: Congenital Heart Disease with Pulmonary Hypertension (CHD-PH) increases Right Ventricular (RV) afterload, which may lead to subclinical myocardial impairment before overt systolic dysfunction becomes apparent. Early detection is crucial to prevent progression to right heart failure. Global Longitudinal Strain (GLS) by echocardiography is sensitive for identifying subclinical RV dysfunction despite preserved conventional systolic parameters, but the role of molecular biomarkers remains unclear. Soluble Suppression of Tumorigenicity 2 (sST2) has been proposed as a potential biomarker for subclinical RV dysfunction. This study aims to compare sST2 levels in CHD-PH patients with and without subclinical RV dysfunction as assessed by RV-Global Longitudinal Strain (RV-GLS). Methods: This cross-sectional study included adult CHD-PH patients (≥18 years) at the Integrated Heart Center, RSUP M. Djamil Padang, from January to June 2025. All participants underwent right heart catheterization and had preserved RV systolic function, as assessed by conventional echocardiography (Three-Dimensional Right Ventricular Ejection Fraction [3D RVEF] ≥45%). RV-GLS was assessed using Speckle-Tracking Echocardiography (STE), and serum sST2 levels were measured. Patients were categorized into subclinical RV dysfunction (GLS > –20%) and without subclinical RV dysfunction (GLS ≤ –20%) groups. Statistical analysis was performed to compare sST2 levels between groups. Results: Thirty-four patients were included (82% female, mean age 37.8 ± 15.6 years), with secundum Atrial Septal Defect (ASD) as the most common etiology (71%). Median sST2 levels in patients with CHD-PH without subclinical RV dysfunction were 15.65 (6.05–40.90) ng/mL, with a GLS of –20.50 (–27.20 to –20.00)%. In patients with CHD-PH with subclinical RV dysfunction, median sST2 was 15.15 (5.25–47.60) ng/mL, with a GLS of –11.80 (–19.90 to –6.20)%. No statistically significant difference in sST2 levels was observed between groups (p = 0.89). In contrast, patients with CHD-PH with subclinical RV dysfunction exhibited significantly higher indexed Pulmonary Arterial Resistance (PAR) and pulmonary-to-Systemic Vascular Resistance ratio (PAR/SVR ratio), indicating increased pulmonary vascular load despite preserved conventional RV systolic function. Conclusion: sST2 levels did not differ significantly between CHD-PH patients with subclinical RV dysfunction and those without. Subclinical RV dysfunction was associated with higher pulmonary vascular load, as reflected by increased indexed PAR and PAR/SVR ratio, despite preserved conventional RV systolic function. From this may conclude that subclinical RV myocardial impairment in CHD-PH is more closely related to hemodynamic afterload than to molecular stress biomarkers alone. These findings suggest that sST2 alone may have limited utility as a biomarker for detecting subclinical RV myocardial impairment in this population.